Asserting Journalistic Autonomy in the 'Post-truth' Era of 'Alternative Facts': Lessons from Reporting on the Orations of a Populist Leader. (June 2017) - Romano, Angela
A current challenge for journalists is how to report on post-truth political discourse in an era when the statements of populist leaders are increasingly characterized by emotionalism, out-of-context use of verifiable facts, euphemisms and double speak. A case study of the much-reported maiden speech by populist leader Pauline Hanson to the Australian Senate in 2016 is used to identify trends and patterns in stories that resulted from her oration. The case study findings were used to distil nine recommendations for journalists about how to research and report on statements by high-profile political and opinion leaders who peddle suspected alternative facts and post-truth logic. The findings indicate a need for journalists to reassert their autonomy over storytelling agendas through decoding post-truth discourse to identify underlying news issues, then applying rigour in certain fundamentals of fact checking, information sourcing, framing and backgrounding of stories. The case study findings have international relevance because the politics and media-management strategies of Hanson and her One Nation party replicate those of populist opinion leaders in the United States, United Kingdom and many other countries.